Impact of on-site cardiac catheterization on resource utilization and fatal and non-fatal outcomes after acute myocardial infarction - Richard Hugues; Eisenberg Mark J; Beck Christine A; Halabi Abdul R; Pilote Louise (BMC, 2006)
Abstract Background Patterns of care for acute myocardial infarction (AMI) strongly depend on the availability of on-site cardiac catheterization facilities. Although the management found at hospitals without on-site catheterization does not lead to increased mortality, little it known about its impact on resource utilization and non-fatal outcomes. Methods We identified all patients (n = 35,289) admitted with a first AMI in the province of Quebec between January 1, 1996 and March 31, 1999 using population-based administrative databases. Medical resource utilization and non-fatal and fatal outcomes were compared among patients admitted to hospitals with and without on-site cardiac catheterization facilities. Results Cardiac catheterization and PCI were more frequently performed among patients admitted to hospitals with catheterization facilities. However, non-invasive procedures were not used more frequently at hospitals without catheterization facilities. To the contrary, echocardiography [odds ratio (OR), 2.04; 95% confidence interval (CI), 1.93-2.16] and multi-gated acquisition imaging (OR, 1.24; 95% CI, 1.17-1.32) were used more frequently at hospitals with catheterization, and exercise treadmill testing (OR, 1.02; 95% CI, 0.91-1.15) and Sestamibi/Thallium imaging (OR, 0.93; 95% CI, 0.88-0.98) were used similarly at hospitals with and without catheterization. Use of anti-ischemic medications and frequency of emergency room and physician visits, were similar at both types of institutions. Readmission rates for AMI-related cardiac complications and mortality were also similar [adjusted hazard ratio, recurrent AMI: 1.02, 95% CI, 0.89-1.16; congestive heart failure: 1.02; 95% CI, 0.90-1.15; unstable angina: 0.93; 95% CI, 0.85-1.02; mortality: 0.99; 95% CI, 0.93-1.05)]. Conclusion Although on-site availability of cardiac catheterization facilities is associated with greater use of invasive cardiac procedures, non-availability of catheterization did not translate into a higher use of non-invasive tests or have an impact on the fatal and non-fatal outcomes available for study in our administrative database.